Wilms Tumor 1b Expression Defines a Pro-regenerative Macrophage Subtype and Is Required for Organ Regeneration in the Zebrafish - Andrés Sanz-Morejón; Ana B. García-Redondo; Hanna Reuter; Inês J. Marques; Thomas Bates; María Galardi-Castilla; Andreas Große; Steffi Manig; Xavier Langa; Alexander Ernst; Indre Piragyte; Marius-Alexandru Botos; et al. (Cell Reports, 2019)
Summary: Organ regeneration is preceded by the recruitment of innate immune cells, which play an active role during repair and regrowth. Here, we studied macrophage subtypes during organ regeneration in the zebrafish, an animal model with a high regenerative capacity. We identified a macrophage subpopulation expressing Wilms tumor 1b (wt1b), which accumulates within regenerating tissues. This wt1b+ macrophage population exhibited an overall pro-regenerative gene expression profile and different migratory behavior compared to the remainder of the macrophages. Functional studies showed that wt1b regulates macrophage migration and retention at the injury area. Furthermore, wt1b-null mutant zebrafish presented signs of impaired macrophage differentiation, delayed fin growth upon caudal fin amputation, and reduced cardiomyocyte proliferation following cardiac injury that correlated with altered macrophage recruitment to the regenerating areas. We describe a pro-regenerative macrophage subtype in the zebrafish and a role for wt1b in organ regeneration. : Sanz-Morejón et al. identify Wilms tumor 1b (Wt1b)+ macrophages with a pro-regenerative gene signature in injured fins and hearts in the zebrafish. They show that Wt1b controls macrophage migration and differentiation. Regeneration is impaired in wt1b mutants, supporting a role for this gene, likely within macrophages, in organ regeneration. Keywords: heart regeneration, zebrafish, macrophages, Wilms tumor 1b, fin regeneration